Effect of functional badminton games on basic motor skills and sensory integration in 5–6-year-old preschool children: A randomised controlled trial - Kang Zhang; Wei Zhang; Wenzhi Ding; Sha Cao (PLoS ONE, 2025)
Objective This study aimed to develop functional badminton games for preschool children and investigate their efficacy in promoting basic motor skills and sensory integration. Methods Sixty children aged 5–6 years were randomly assigned to an experimental group or a control group. The experimental group received a 12-week intervention consisting of functional badminton games, while the control group participated in regular physical activities. Measures of physical fitness, basic motor skills, and sensory integration were assessed at baseline and post-intervention. Results The control group demonstrated significant improvements in the grip test, 15-meter steeplechase test, sit-and-reach test, standing long jump, locomotor subtest, ball skills subtest, and proprioception ( P < 0.01). The experimental group demonstrated significant enhancements in BMI, grip test, 15-meter steeplechase test, sit-and-reach test, standing long jump, vestibular function, tactile defensiveness, proprioception ( P < 0.01). All basic motor skill indicators in the experimental group exhibited significant improvements ( P < 0.01) with large effect sizes ( d > 0.80). Between-group comparisons revealed that the experimental group achieved significantly greater improvements in locomotor subtest, ball skills subtest, and vestibular function( P < 0.0167). Conclusion Functional badminton games effectively enhance physical fitness, promote healthier BMI, and improve basic motor skills and sensory integration in preschool children. While regular physical activities also improve physical fitness, basic motor skills and proprioception, but they demonstrate limited effects on balance, BMI, vestibular function, tactile defensiveness, and learning ability. The findings indicate that functional badminton games are superior to conventional physical activities in enhancing basic motor skills and sensory integration, representing a valuable approach for promoting motor development in preschool children.